Baastrup’s Disease, a Rare Cause of Cauda Equina Syndrome: Case Report - Aniruddha Vaidya; Sushil Mankar; Nitin Pothare; Vismay Harkare (Journal of Orthopaedic Case Reports)
Introduction: Baastrup’s disease, more commonly known as kissing spines, has been implicated as a cause for low back pain and extension of the synovial cavity to the intraspinal space, resulting in extradural compression. However, this is the first report in the literature of a cyst responsible for cauda equina syndrome. Case Report: We present a case of a 60-year-old male having an epidural synovial cyst as an extension of Baastrup’s disease, causing cauda equina syndrome, and to review the relevant literature. Radiographs were normal, and magnetic resonance imaging showed the presence of a cyst in the posterior epidural space at the L4-L5 level causing dural compression. Moreover, the cysts were excised, and spinal decompression was performed. The patient had good relief of symptoms. Conclusion: This case highlights the importance of considering Baastrup’s disease as a potential, though uncommon, cause of neurological deficits in patients presenting with cauda equina syndrome. Early diagnosis and prompt surgical decompression are critical to improving neurological outcomes and preventing long-term complications.